The Irish regiments in the Great War : discipline and morale - Bowman, Timothy (Manchester University Press ; Distributed exclusively in the USA by Palgrave, 2003)
A comprehensive study of discipline and morale in the British army during the Great War, using the Irish regiments as a case study. The book suggests that, while minor breaches of discipline did occur in the Irish regiments, executions took place out of the need to restore military discipline.